Site-Specified Two-Dimensional Heterojunction of Pt Nanoparticles/Metal-Organic Frameworks for Enhanced Hydrogen Evolution - Wang, Mengjun; Xu, Yong; Peng, Chun-Kuo; Chen, San-Yuan; Lin, Yan-Gu; Hu, Zhiwei; Sun, Li; Ding, Songyuan; Pao, Chih-Wen; Shao, Qi; Huang, Xiaoqing (Journal of the American Chemical Society, 2021)
Heterojunction nanostructures usually exhibit enhanced properties in compariosn with their building blocks and are promising catalyst candidates due to their combined surface and unique interface. Here, for the first time we realized the oriented growth of ultrasmall metal nanoparticles (NPs) on metal-organic framework nanosheets (MOF NSs) by precisely regulating the reduction kinetics of metal ions with solvents. In particular, a rapid reduction of metal ions leads to the random distribution of metal NPs on the surface of MOF NSs, while a slow reduction of metal ions results in the oriented growth of NPs on the edge of MOF NSs. Impressively, the strong synergy between Pt NPs and MOF NSs significantly enhances the hydrogen evolution reaction (HER) performance, and the optimal catalyst displays HER activities superior to those of a composite with a random growth of Pt NPs and commercial Pt/C under both acidic and alkaline conditions. Moreover, the versatility of such oriented growth has been extended to other metal NPs, such as Pd, Ag, and Au. We believe this work will promote research interest in material design for many potential applications.Heterojunction nanostructures usually exhibit enhanced properties in compariosn with their building blocks and are promising catalyst candidates due to their combined surface and unique interface. Here, for the first time we realized the oriented growth of ultrasmall metal nanoparticles (NPs) on metal-organic framework nanosheets (MOF NSs) by precisely regulating the reduction kinetics of metal ions with solvents. In particular, a rapid reduction of metal ions leads to the random distribution of metal NPs on the surface of MOF NSs, while a slow reduction of metal ions results in the oriented growth of NPs on the edge of MOF NSs. Impressively, the strong synergy between Pt NPs and MOF NSs significantly enhances the hydrogen evolution reaction (HER) performance, and the optimal catalyst displays HER activities superior to those of a composite with a random growth of Pt NPs and commercial Pt/C under both acidic and alkaline conditions. Moreover, the versatility of such oriented growth has been extended to other metal NPs, such as Pd, Ag, and Au. We believe this work will promote research interest in material design for many potential applications.